Technological Advancement: Issues, Challenges and Perspectives for Human Resource Practice in Nigeria - Bawalla, Oluwatoyin Gbenga; Rufai, Daniel Omolola (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
The adoption of modern technology in the 21 st century poses considerable threat to most developing countries such as the environmental factors like economic system and level of development as the bane affecting domestic organisation. This has shaped human resource management and employment relations in most organisations in Nigeria. The study adopted System Theory by Talcott Parsons which sees organization as sub-system that interacts within a given environment (products, services and information) on how human resource practitioners are seen as the link to have requisite personnel experts in handling the operations of the organisations. The paper revealed that human resource management is challenged with effective performance, diversity in employees’ values, federal character and economic downturn. However, for effective and efficient human resource management in the 21 st century, the paper recommended that the human resource practitioners should upgrade the human resource professional skills, provision of requisite expertise of personnel in handling affairs of the organisations as well as utilisation of information technology. Keywords: Human Resource Management, Human Resource Practitioners, Organisations, Technology, 21st Century